Kebijakan Program Pemberdayaan Masyarakat Industri: Studi Kasus Implementasi Program Tegal Bisnis - Zainudin, Arif; Suranto, Suranto (Journal of Governance and Public Policy, 2014)
The purpose of  this study is to look at the impact of  the implementation of the policy Business Tegal. In evaluating the program Business Tegal viewed from the aspect of  productivity policy, financial efficiency and level of  community satisfaction policy Business Tegal. By using a mixed method research approach hopes this research can include aspects of  qualitative and quantitative. Based on the results of  research carried out showed that the productivity of the policy can not boost industrial production and the quality of  many of  the home industry go bankrupt due to the government can not provide assistance in the form stimulant funds. Although the government has provided some training still can not help improve the quality of  the industry because the training is not only limited to assisting the industry as expected by the public. With the impact, then the public is not satisfied about the implementation of  the Business Tegal policy because no positive impact on the sustainability of  the industry and welfare.